What are the perceptions of healthy food choices? A cross-sectional study from Saudi Arabia - A. Alissa, Nawal (Italian Journal of Food Science, 2024)
Previous studies conducted in Saudi Arabia demonstrated dietary patterns or energy/nutrient intakes with limited information about Saudi’s perception about healthy food choices. Insights in the perceptions of healthy food choices are critical for developing targeted interventions to support Saudi population with the goal of improving healthy eating behaviors and, as a result, lowering the risk of diet-related diseases. Therefore, this study aimed to assess knowledge, attitude as well as the practice of people about healthy food choices in Saudi Arabia. The study employed a descriptive cross-sectional design with 303 participants included in the analysis. The population settings were at three primary healthcare centers in Tabuk city of Saudi Arabia. Data were collected through self-administered paper–pencil surveys to assess the knowledge, attitude, and practices of healthy food choices. Data were analyzed using the SPSS statistical software version 26. The results revealed that participants in this study performed above average in terms of their perceptions (knowledge, attitude, and practice) of healthy food choices. The major findings of this study showed that statistically significance difference was found between the place of residence in relation to the practices of healthy food choices (F 7,238 and p < 0.05). A significant association was observed between knowledge of healthy food choices and marital status. Multiple comparisons post hoc tests indicated that the married group was a significantly different group at α = 0.044. Additionally, the relationship between monthly income groups and attitudes was statistically significant, with p < 0.05. Findings of this study could assist health educators in developing appropriate programs, awareness messages, and community campaigns to improve perceptions about healthy food choices. The findings observed that considering why practicing healthy food choices that could lower the risk of diseases and promote optimal health could be a challenge.